2022
DOI: 10.48550/arxiv.2208.04162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Information Transfer in Stochastic Biochemical Networks

Abstract: We develop numerical and analytical approaches to calculate mutual information between complete paths of two molecular components embedded into a larger reaction network. In particular, we focus on a continuoustime Markov chain formalism, frequently used to describe intracellular processes involving lowly abundant molecular species. Previously, we have shown how the path mutual information can be calculated for such systems when two molecular components interact directly with one another with no intermediate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In fact, because the transcription factor profiles are time-varying, the input signals and the corresponding output signals compose the complete trajectories of the input and output processes on a considered time interval [0, t]. In [42,43], it was shown that the mutual information can be used to quantify the cumulative amount of information exchanged along these trajectories. In the present work, we introduced the joint time sequence Z to describe the trajectories of the input and output processes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, because the transcription factor profiles are time-varying, the input signals and the corresponding output signals compose the complete trajectories of the input and output processes on a considered time interval [0, t]. In [42,43], it was shown that the mutual information can be used to quantify the cumulative amount of information exchanged along these trajectories. In the present work, we introduced the joint time sequence Z to describe the trajectories of the input and output processes.…”
Section: Discussionmentioning
confidence: 99%